Analysis of risk factors associated with secondary open-angle glaucoma in Posner-Schlossman syndrome: A retrospective case-control study - Li, Jiajun; Ji, Yuke; Yang, Weihua; Yao, Yujia; Wang, Suyu; Zhang, Ziran; Yao, Jin; Li, Keran (Frontiers in Medicine, 2023)
Background: Posner-Schlossman syndrome (PSS) is a relatively rare cause of chronic secondary open-angle glaucoma (OAG), but the exact cause is unknown. This study aimed to determine potential risk factors for OAG secondary to PSS and to provide a basis for early intervention in the development of PSS. Methods: This was a retrospective case-control study. Nine cases diagnosed with PSS and seven cases diagnosed with OAG secondary to PSS were selected and aqueous humor was collected prior to treatment. Clinical characteristics including age, sex, eye laterality, baseline visual acuity, maximum IOP, corneal endothelial cell density, visual field, retinal nerve fiber layer thickness, cup-to-disc ratio, keratic precipitates, anterior chamber inflammation, and aqueous humor cytokine assay results were compared between the two groups. Results: The cytomegalovirus (CMV) positivity was 55.60% (5/9) in patients with PSS and 100% (7/7) in patients with OAG secondary to PSS. Corneal endothelial cell density was lower in patients with CMV-positive PSS (p = 0.0116). Basic fibroblast growth factor (bFGF), interleukin (IL)-6, and vascular cell adhesion molecule (VCAM) concentrations were higher than standard reference values in patients with PSS; IL-8, IL-6, and VCAM concentrations were higher than standard reference values in patients with OAG secondary to PSS; and IL-8 concentrations were significantly higher in patients with OAG secondary to PSS (p = 0.0229). There were significant positive correlations between IL-8 and IL-6, IL-6 and VCAM (p = 0.0304, p = 0.0172) and a significant negative correlation between bFGF and vascular endothelial growth factor (VEGF) (p = 0.0497). Simultaneous increase in IL-8 and IL-6 concentrations could be used as a cytokine indicator to predict secondary OAG in patients with PSS (p = 0.0095). Conclusion: Simultaneous increase of IL-8 and IL-6 concentrations may be an important cause of accelerated secondary OAG in patients with PSS, with IL-8 playing a more critical role. IL-8 and IL-6 may be a more reliable cytokine marker for predicting secondary OAG in PSS, but the high likelihood of subsequent OAG in patients with CMV-positive PSS should not be ignored. Regulation of IL-8 and IL-6 levels may be a new strategy of preventing OAG secondary to PSS.